Analisis Work Engagement Pada Karyawan PrimeBiz Hotel Surabaya - Anshori, Mohammad Yusak; Karya, Denis Fidita (Jurnal Ilmiah Pariwisata, 2018)
Work engagement is one of the important component in the organization that can drive the optimal organizational performance. Work engagement also related to the outcome performance such as productivity, profitability, and customer loyalty. The aim of this research to find out the factors that influence work engagement at PrimeBiz Hotel Surabaya. This research using quantitative method with the saturation sampling technique. The sample of this research were 45 employees that has been working more than a year at PrimeBiz Hotel Surabaya. The result of the result was financial compensation influenced to the work engagement, financial compensation influenced to the organizational commitment, and organizational commitment influenced to the work engagement.